Syok Hipovolemik pada Plasenta Previa - Fina Fatmawati Prayitno; Nurul Islamy; M. Zulkarnain Hussein; Marzuqi Sayuti (CV. Jasa Sukses Abadi, 2020)
Placenta previa is associated with increased maternal and fetal morbidity and mortality, especially if caused by continuous bleeding, making an accurate diagnosis is very important. The incidence of hypovolemic shock in placenta previa is very likely to occur when bleeding occurs continuously and is not managed accordingly. A 31-years-old woman, G2P1A0 30 weeks, presents with vaginal bleeding without pain. In obstetric examination, it was found that the results of the inspection contained vaginal bleeding, the results of the inspecular were positive fluxes with inactive blood from the external uterine ostium. Laboratory investigations found that the hemoglobin level was 10.2 g / dl. The patient was diagnosed with placenta previa totalis via ultrasonography. During the treatment the patient experienced worsening of symptoms resulting in hypovolemic shock. Management of these patients is carried out immediately and consideration of termination of pregnancy. Proper diagnosis and management will be the modality of reducing maternal and fetal morbidity and mortality. End a pregnancy when symptoms worsen, should always be considered an option in the treatment of placenta previa even though the pregnancy is not yet months.